Exposure to particulate matter and cardiovascular disease risk - Nowicka, Grażyna (Studia Ecologiae et Bioethicae, 2007)
Epidemiological studies clearly indicate that both long- and short-term exposure to several environmental air pollutants cause significant increase in the risk of cardiovascular events, the observed strong relation between particulate matter air level and cardiovascular diseases may be explained by indirect or direct influence of these particles on different biological processes involved in disease development. Improvement of air quality standards and lowering of particulate matter exposure can significantly diminish cardiovascular disease risk and improve public health status.